(untitled) (TAMADDUN NURI JURNALI, 2024)
This article analyzes the theoretical and moral foundations of democratization and civil society oversight in Uzbekistan. Democratic processes, the development of civil society, and the strengthening of relations between the state and society play an important role in ensuring social well-being and legal justice. Additionally, the development of national and moral values also plays a significant role in shaping a democratic society.